Evalusi Kualitas Fungsional Sistem Persediaan Penjuaalan Web Dengan Blackbox dan UAT - Nenden Nuraini; Andi Ode Larios; Andhika Pramudya; Tundo (Universitas Siber Indonesia, 2026)
This study evaluates the functional quality of a web-based inventory and sales information system by integrating Black Box Testing and User Acceptance Testing (UAT). These two methods were applied to 32 test cases covering authentication, master data, purchasing, and sales modules, resulting in 27 successful cases and an overall success rate of 84.38%. The remaining five cases revealed several limitations, namely the unavailability of CSV data export in four modules, the absence of a delivery-order feature, and the lack of validation to prevent negative stock in sales transactions. UAT involved nine store users through daily work scenarios and a five-point Likert questionnaire covering functional suitability, usability, reliability, efficiency, and overall satisfaction. The UAT results showed an overall mean score of 4.2 (“Good”), with the highest score in the reliability dimension (4.5) and the lowest in the efficiency dimension (3.9). In general, users considered the system adequate to support basic operations, but still requiring reporting flexibility and safeguards against input errors. These findings indicate that the combination of Black Box Testing and UAT is effective in identifying gaps between technical specifications and operational needs, and provides a basis for recommendations to improve web-based inventory and sales systems in small retail environments.